Salivary Antioxidant Capacity and Oral Health Status in Children with Visual Impairments—A Cross-Sectional Study - Hazra, Madhurima; Shetty, Vabitha; Suresh, Lekshmi Radhakrishnan (Journal of Health and Allied Sciences NU, 2022)
Background Children with visual impairment are at a higher risk for developing dental disease, and imbalances in the antioxidant levels may play an important role in the development and management of oral diseases.Aim Our aim was to evaluate and compare the oral health status and salivary total antioxidant capacity (TAC) in children with and without visual impairment.Methods Oral health was evaluated among 6 to 11 years old children with and without visual impairment (50 each) using World Health Organization oral health assessment form for caries prevalence, gingival health, and oral hygiene levels. Unstimulated saliva was collected and assayed for TAC using the phosphomolybdic method.Statistical Analysis The data collected were tabulated, and the results, thus, obtained were subjected to statistical analysis using EZR software—version 1.37. The variables between the two groups were compared using the Mann–Whitney U test and Fisher's exact test. A correlation test was done using Spearman's correlation test.Results The mean TAC levels among children with and without visual impairment were 49.17 (±25.702) and 156.67 (±56.031) µg/mL, respectively, which was statistically significant (p < 0.001). The children with visual impairment showed a significantly higher number of carious lesions compared with the control group (p < 0.001). Oral hygiene status and gingival health status were significantly poorer in children with visual impairments than the children in the control group (p < 0.001).Conclusions Oral health was significantly poorer, and salivary TAC levels were significantly lower in children with visual impairment. There may be an inverse correlation between salivary TAC and oral health status. Clinical Significance: Since these children have been shown to have poorer oral health status, a baseline assessment of their salivary antioxidant capacity may indicate the need to reinforce oral care efforts and supplement them using an antioxidant-rich diet.
Keywords: dental caries; gingivitis; free radicals; antioxidants; visual impairment